Understanding powder bed fusion additive manufacturing phenomena via numerical simulation (Fracture and Structural Integrity, 2020)
The increasing interest in additively manufactured metallic parts from industry has issued a formidable challenge to the academic and scientific world that is asked to design new alloys, optimize process parameters and geometry as well as guarantee the reliability of a new generation of load-bearing components.Unfortunately, understanding the interaction between different phenomena associated to metal-additive manufacturing processes is a very difficult task. In this scenario, numerical modelling emerges as a valid technique to face problems related to the influence of process parameters on metallurgical and mechanical properties of additively manufactured components.This contribution is aimed at summarizing the most important outcomes about metal-additive manufacturing process obtained via numerical simulation with particular reference to powder bed fusion techniques. The fundamentals of additive manufacturing numerical simulation will be also explained in detail. Thermal, metallurgical as well as mechanical aspects are covered.
Keywords: Additive manufacturing; Powder bed fusion process; Numerical simulation; Microstructure; Defects; Residual stress